Analysis of Employee Performance in Providing Administrative Services to the Community (Case Study at the Karang Baru Village Office, Selaparang District, Mataram City, West Nusa Tenggara Province) - Dianti, Ira (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The essence of performance is a result achieved by employees in carrying out their tasks or work efficiently and effectively. In terms of administrative services, these are services that produce various forms of official documents needed by the community. The problem in this research is that the performance of employees at the sub district office is not optimal in providing administrative services to the community at the Karang Baru Sub district office, Selaparang District, Mataram City, West Nusa Tenggara Province. The aim of this research is to determine the performance of sub-district office employees who are not yet optimal in providing administrative services to the community in Karang Baru sub-district. This research uses a qualitative approach and data collection methods using interviews, observation and documentation. Based on the research results, it is known that the performance of employees at the Karang Baru sub-district office is still less than optimal in providing administrative services to the community.